DEVELOPMENT OF A SOFTWARE SYSTEM FOR SEARCHING FOR LOST ITEMS - Solovei, I.; Vorochek, O. (Municipal economy of cities. Series: «Economy science», 2024)
The article presents an approach to developing a software system to facilitate the efficient search for lost items. As part of the study, the authors designed an integrated system that includes server, web, and mobile versions, which provides broad opportunities for identifying and returning lost property. In large urban agglomerations, the loss of personal items becomes a common problem. Existing solutions are often limited to preventive measures and do not provide sufficient support after the item’s loss. The lack of an effective feedback and identification system complicates the lost property search process. The developed system uses modern technologies such as Django for the backend, JavaScript for the web interface, and Flutter for creating cross-platform mobile applications. This approach makes it possible to expand the list of system users to the maximum extent. Django, a capable web framework, facilitates reliable data management and integration with various interfaces. The study involved the development of a database to provide storage and processing of all the necessary information. Using REST API ensured efficient interaction between the system’s server, web, and mobile parts. This approach allows different system components to exchange data in a unified format. The system lets users register individuals and legal entities, which makes it possible to use it in a wide range of public spaces. It helps to effectively search for and return lost items on the street and in public places, including restaurants, theatres, and transport hubs where lost items often occur. The software system created in this study addresses the critical problem of losing personal items. Widespread use of this system across various sectors could dramatically improve managing lost and found operations, turning a typically disorganised and ineffective process into an efficient, technology-driven one. The system’s implementation has the potential to significantly reduce the time and resources spent on searching for lost property and increase the productivity of lost property offices.